2009
DOI: 10.1242/dev.031195
|View full text |Cite
|
Sign up to set email alerts
|

Formation of thebicoidmorphogen gradient: an mRNA gradient dictates the protein gradient

Abstract: The Bicoid (Bcd) protein gradient is generally believed to be established in pre-blastoderm Drosophila embryos by the diffusion of Bcd protein after translation of maternal mRNA, which serves as a strictly localized source of Bcd at the anterior pole. However, we previously published evidence that the Bcd gradient is preceded by a bcd mRNA gradient. Here, we have revisited and extended this observation by showing that the bcd mRNA and Bcd protein gradient profiles are virtually identical at all times. This con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
252
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(278 citation statements)
references
References 48 publications
25
252
1
Order By: Relevance
“…1,2,4 A large number of experimental and theoretical investigations on the formation and functioning of morphogen gradients has appeared in recent years. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]21,22 However, many aspects of biological signaling remain not well understood. 4,6 One of the most important problems of the biological development is to understand the mechanisms of the morphogen gradients formation.…”
Section: Figure 0: Toc Graphicmentioning
confidence: 99%
“…1,2,4 A large number of experimental and theoretical investigations on the formation and functioning of morphogen gradients has appeared in recent years. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]21,22 However, many aspects of biological signaling remain not well understood. 4,6 One of the most important problems of the biological development is to understand the mechanisms of the morphogen gradients formation.…”
Section: Figure 0: Toc Graphicmentioning
confidence: 99%
“…In this model, the process of Bcd gradient formation and its final shape are dictated by the redistribution process of bcd mRNA. 14,15 We refer to this model as the mRNAdictated-gradient model. Since the measured bcd mRNA profile differs from the exponential Bcd protein profile, 14 the pure form of the proposed mRNA-dictatedgradient model also appears inadequate for explaining fully how the Bcd protein gradient is formed.…”
Section: Morphogen Gradient Formation and Actionmentioning
confidence: 99%
“…14,15 We refer to this model as the mRNAdictated-gradient model. Since the measured bcd mRNA profile differs from the exponential Bcd protein profile, 14 the pure form of the proposed mRNA-dictatedgradient model also appears inadequate for explaining fully how the Bcd protein gradient is formed. 12,16 In addition to these two contrasting models, several other models have also been proposed for Bcd.…”
Section: Morphogen Gradient Formation and Actionmentioning
confidence: 99%
“…1 bcd is localized to the anterior of the egg through its 3'UTR. 2 Recently, it was found that the mRNA is released from the anterior pole of the embryo and forms a gradient, 3 which upon translation gives rise to the anterior/posterior (AP) gradient of Bcd protein. 4 Bcd is a homeodomain containing transcriptional activator and regulates target gene transcription in a concentration dependent fashion.…”
mentioning
confidence: 99%